Incorrect drug selection at the point of dispensing: a study of potential predisposing factors. - Anto, Berko; Barlow, David; Oborne, C. Alice; Whittlesea, Cate (International Journal of Pharmacy Practice, 2011)
Objective To determine potential predisposing factors to medication errors involving confusion between drug names, strengths and dosage forms. Methods The study analysed medication errors reported over the period January 2005 to December 2008 from the two main dispensaries of a 1200-bed NHS Foundation Hospital Trust in London. Dispensing incidents considered for analysis included all incidents involving drug name, strength and dosage label and content errors. Statistical analyses were performed using Statistica. Dispensing frequencies of the prescribed and wrongly dispensed drugs were compared by means of Wilcoxon signed-rank test, and the extent of correlation between dispensing frequency and error frequency was assessed using Spearman's rank correlation coefficient. Key findings The Trust recorded a total of 911 dispensing errors between 2005 and 2008. The most significant category, which accounted for 211 (23.2%) of the reported errors, involved errors in drug selection. Drug-selection errors were not random events because the plot of error frequency against the average yearly dispensing frequency for the 1000 most issued drugs showed little evidence of association ( r = 0.19, P(α) = 0.03). There was, however, an increased likelihood of drug-selection errors occurring when the prescribed drug was dispensed with relatively low frequency and shows a significant orthographic similarity to another drug which has a higher dispensing frequency. Conclusion The majority of drug-selection errors would seem to be caused by insufficient attention paid to the specified drug strength. Dispensing frequency is an important factor influencing the likelihood of a drug-selection errors occurring, but it is also shown here that a large proportion of the drug-selection errors involved specifications exhibiting high orthographic similarity.